Vernacular memorialization in the military: personal acts of remembrance at RAF Thorpe Abbotts. Issue 2 (2nd September 2019) - Gregory, Derwin
ABSTRACT: In September 2017, an archaeological excavation at RAF Thorpe Abbotts (also known as Station 139) uncovered 7 identification 'dog' tags belonging to airmen of the United States Army Air Force (USAAF). It is the thesis of this article that these were purposefully buried by individuals within the 100th Bomb Group (Heavy) as acts of remembrance. Alongside the dog tags were a number of other artefacts, including coins, bottles, and a canteen cup. These likely formed the material culture of self-developed grieving rituals established by the primary group responsible for the deposition of the dog tags.